Fungal keratitis - Tuli, Sonal S (Dove Medical Press, 2011)
CLINICAL QUESTION: What is the most appropriate management of fungal keratitis? RESULTS: Traditionally, topical Natamycin is the most commonly used medication for filamentous fungi while Amphotericin B is most commonly used for yeast. Voriconazole is rapidly becoming the drug of choice for all fungal keratitis because of its wide spectrum of coverage and increased penetration into the cornea. IMPLEMENTATION: Repeated debridement of the ulcer is recommended for the penetration of topical medications. While small, peripheral ulcers may be treated in the community, larger or central ulcers, especially if associated with signs suggestive of anterior chamber penetration should be referred to a tertiary center. Prolonged therapy for approximately four weeks is usually necessary.